Community Participation Relationship with Flood Disaster Mitigation in Boliyohuto District, Gorontalo District - Pipin Yunus; Zuriati Muhamad; Sabirin B Syukur (Journal of Community Health Provision, 2021)
Disaster is the incident or sequence which threatens and disrupts people’s lives that caused of natural and non natural factors as well as human factors resulting in fatalities environmental damage, and property loss. The objective of research was to determine the relationship between society’s participations with flood disaster mitigation at Tolite village, Boliyohuto sub district. The design used quantitative descriptive with cross sectional study approach. The populations are 1101 respondents of societies with sampling was used purposive sampling technique with the samples determinate used slovin formula therefore obtained the samples are 92 respondents. Statistical test used chi square. With significance value is p value= 0,005 small than (p<0,05) thus Ho is rejected and Ha is accepted. Concluded, there is significance relationship between between society’s participations with flood disaster mitigation at Tolite village, Boliyohuto sub district.